Sporadic Hemiplegic Migraine with Seizures and Transient MRI Abnormalities - Harsha Bhatia; Fawzi Babtain (Case Reports in Neurological Medicine)
Hemiplegic migraines are characterised by attacks of migraine with aura accompanied by transient motor weakness. There are both familial and sporadic subtypes, which are now recognised as separate entities by the International Classification of Headache Disorders, edition II (ICHD-II). Sporadic hemiplegic migraine is a rare variant of migraine, We report a case of sporadic hemiplegic migraine and seizures with MRI features suggestive of cortical hyper intensity and edema on T2 and FLAIR images with no restriction pattern on diffusion and these changes completely resolving over time, suggesting that these changes are due prolonged neuronal depolarization and not of ischemic origin.